(untitled) (Revista de Crítica Literaria Latinoamericana, 2025)
Orígenes Lessa (1903-1986), elected member of the Brazilian Academy of Letters in 1981, was a highly awarded writer. One of his novels, O Feijão e o Sonho, was adapted for television and shown between June and October 1976 on Rede Globo. Lessa wrote stories that identify with science fiction and fantasy stories and novels that move between the fantasy genre and the fantasy modality. Despite this, the author and his work have been forgotten for years and there is no movement to rescue them. The short story “A gargalhada”, that is the objet of this essay, can be read both as science fiction and, more appropriately, as fantastic, especially if approached from a modal perspective.